Investigation of phthalate metabolites in urine and daily phthalate intakes among three age groups in Beijing, China. (May 2020) - Zhang, Xu; Tang, Song; Qiu, Tian; Hu, Xiaojian; Lu, Yifu; Du, Peng; Xie, Linna; Yang, Yanwei; Zhao, Feng; Zhu, Ying; Giesy, John P.
Abstract: Phthalates are widely used as binders and plasticizers in industrial and consumer products but show diverse toxicity. We investigated the level of human exposure to phthalates in Beijing, one of the most densely populated cities in the world. In this study, 12 metabolites of phthalates were measured in 70 spot urine samples collected from Beijing residents from August 2017 to April 2018 using ultra high-performance liquid chromatography tandem mass spectrometry. We found that metabolites of phthalates were ubiquitous in all urine samples. Total concentrations of phthalate metabolites ranged from 39.6 to 1931 ng mL −1, with median concentrations were in decreasing order of children (371 ng mL −1 )> younger adults (332 ng mL −1 )> older adults (276 ng mL −1 ). Mono-n-butyl phthalate (MnBP) was the predominant compound, and occurred at concentrations greater than those reported for people in other countries. The mean values of estimated daily intakes (EDIs) of ∑phthalate were 35.2, 10.3 and 10.9 ng (kg-bm) −1 d −1 for children, younger adults and older adults, respectively. EDIs of di-n-butyl phthalate (DnBP), di-iso-butyl phthalate (DiBP) and di-(2-ethylhexyl) phthalate (DEHP) exceeded reference values suggested by the US Environmental Protection Agency and the European Food Safety Authority. When concentrations were normalized to volume or creatinine-adjusted, hazard quotients (HQs) for 40 of 70 participants exhibited larger HQs >1 for individual phthalates, which was indicative of potential for adverse effects. Thus, exposure to phthalates might be a critical factor contributing to adverse health effects in Beijing residents. To the best of our knowledge, this is the first study to establish a pre-baseline level of urinary phthalate metabolites among residents in Beijing. Graphical abstract: Image 1 Highlights: Residents of Beijing are ubiquitously exposed to PAEs. MnBP is the predominant compound in urine with the highest level worldwide. Children are exposed to higher levels of PAEs than the younger adults and older adults. Most individuals from Beijing had HIs and HQs that exceeded the threshold of 1.